Self-healable ZnO@ multiwalled carbon nanotubes (MWCNTs) /DA-PDMS nanocomposite via Diels-Alder chemistry as microwave absorber: A novel multifunctional material. (November 2020) - Zhou, Meng; Yan, Qiming; Fu, Qi; Fu, Heqing
Abstract: The combination of microwave absorption performance and self-healing function is of great practical significance. In this paper, first, ZnO@MWCNTs nanoparticle is prepared by loading Zinc oxide (ZnO) on the surface of the multiwalled carbon nanotubes (MWCNTs) as microwave absorbers. Then, the thermoreversible self-healing DA-PDMS is prepared by using polydimethylsiloxane (PDMS) as raw material based on Diels-Alder (DA) reaction. Finally, a kind of novel multifunctional ZnO@MWCNTs/DA-PDMS nanocomposite with self-healing and microwave absorption properties is synthesized with the addition of ZnO@MWCNTs nanoparticle. When the cracked ZnO@MWCNTs/DA-PDMS nanocomposite is maintained at 120 °C for 10 min, it can recover more than 90% of the original mechanical strength. Even after three healing cycles, the ZnO@MWCNTs/DA-PDMS nanocomposite also displays excellent healing efficiency (about 90%). On the other hand, when the content of ZnO@MWCNTs nanoparticle is 10 wt%, ZnO@MWCNTs/DA-PDMS nanocomposite exhibits an effective absorption bandwidth from 8.2 to 12.4 GHz (full X-band) at a thickness of 3 mm and the minimum reflection loss of −20.1 dB. Even after the 3rd healing cycle, the minimum reflection loss of the healed samples can still maintain −20.0  dB at a thickness of 3 mm. ZnO@MWCNTs/DA-PDMS nanocomposite will have good development prospect in the field of intelligence and microwave absorption materials. Graphical abstract: Image 1 Highlights: A self-healing nanocomposite with microwave absorption could be healed at 110 °C for 10 min. The minimum RL of nanocomposite is up to −20.1 dB.